The Essential Oil Component Terpinyl Acetate Alters Honey Bee Energy Levels and Foraging Behavior - Trey Mathews; Ella Joyce; Charles I. Abramson; Harrington Wells; Robert J. Sheaff (Insects)
Essential oils have been utilized in the health, learning/memory, and agricultural fields, but not much is known about the biological activity of their individual components. Terpinyl acetate is a p-menthane monoterpenoid commonly found in cardamom, pine, cajeput, pine needle, and other essential oils. Using a cell culture model system, we found that terpinyl acetate is a potent and specific inhibitor of mitochondrial ATP production, suggesting it might function as a plant toxin. Remarkably, however, terpinyl acetate was not cytotoxic because cells switched to glycolysis to maintain ATP levels. Based on these findings, we hypothesized that terpinyl acetate might be employed to benefit plant survival by modulating metabolism/behavior of plant pollinators such as the honey bee. This hypothesis was tested by investigating terpinyl acetate’s effect on honey bee foraging. Free-flying honey bee flower color choice was recorded when visiting a blue-white dimorphic artificial flower patch of 36 flowers. The nectar–reward difference between flower colors was varied in a manner in which both learning and reversal learning could be measured. Terpinyl acetate ingestion disrupted reversal learning but not initial learning: this change caused bees to remain faithful to a flower color longer than was energetically optimal.